Review of manufacturing process for good quality of composite assessment - Zulkepli, I.I.; Mokhtar, Hanan; Aminanda, Yulfian; Shaik Dawood, Mohd. Sultan Ibrahim; Mohamed Rehan, Muhammad Saifuddin (IOP Publishing Ltd, 2019)
This review paper focuses on the detailed technique and process of fiber fabrication until it becomes composite which is useful for the manufacturing industry. The most famous fabrication methods are the open and closed mould. In general, open mould is a method which exposes the specimen to the atmosphere and the surface condition is not controlled. Close mould, however, is the opposite to open mould, that is in closed conditions without direct contact of the atmosphere and the surface condition is controllable. The manufacturing process techniques are presented comparatively. Discussion on fiber type that is more suitable for specific techniques are also presented in this paper.